Long‐term remission of extramedullary cutaneous relapse of acute myeloid leukaemia (leukaemia cutis) treated with decitabine‐venetoclax - Denise Maravalle; Alessandra Filosa; Catia Bigazzi; Guido Collina; Piero Galieni (eJHaem, 2022)
Abstract In February 2020, a 74‐year‐old female was diagnosed with myelomonocytic acute myeloid leukaemia with FLT3 mutation and blasts positive for CD33, BCL‐2 and CD68/PGM1. Not responding to a standard Cytarabine–containing regimen plus Midostaurin, the patient achieved a complete remission (CR) of the disease in the bone marrow following a reinduction therapy with high‐dose Cytarabine but simultaneously relapsed developing leukaemia cutis with disseminated lesions in 80% of the body surface area. After receiving 10 cycles of Decitabine plus Venetoclax the patient achieved and maintains a continuous CR.